1990
DOI: 10.1007/bf01294110
|View full text |Cite
|
Sign up to set email alerts
|

Collective excitations in148Gd populated in thep p?-reaction on a radioactive target

Abstract: Collective excitations in the two-particle nucleus 14SGd up to 2.9 MeV have been investigated by the pp'-reaction at 25 MeV beam energy, and angular distributions have been analyzed with standard DWBA calculations. It is found that ~48Gd has larger octupole-than quadrupole collectivity in the energy range investigated. The 3strength distribution is in quantitative agreement with predicted results for the levels formed by the coupling of two valence particles to the ~46Gd core octupole phonon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

1990
1990
1990
1990

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…We mention here that the recent (p,p') study [17] with a radioactive ~48Gd target has identified the 32 and 33 states, at 2.234 and 2.917 MeV, both within 20 keV of the predicted energy. III.3, reflecting the coupling to high-lying core excitations.…”
Section: Iv1 the V 2 X 3-excitationssupporting
confidence: 51%
See 3 more Smart Citations
“…We mention here that the recent (p,p') study [17] with a radioactive ~48Gd target has identified the 32 and 33 states, at 2.234 and 2.917 MeV, both within 20 keV of the predicted energy. III.3, reflecting the coupling to high-lying core excitations.…”
Section: Iv1 the V 2 X 3-excitationssupporting
confidence: 51%
“…No other fp multiplet member was observed in the present experiments, but a 2.189 MeV 2 + state rather strongly excited with l=2 in pp' [17] and an/=4 state at 2.763 MeV are good candidates for the fp 2 + and 4 + levels. Moreover, the aK value and the angular distribution data for the 1058 keV 5 + ~ 6 + transition require > 70% E2 content, which gives strong independent support for the fp assignment.…”
Section: Iii1 the V F7z/z Statescontrasting
confidence: 50%
See 2 more Smart Citations